Current and historic patterns of chronic disease burden are associated with physical activity and sedentary behavior in older adults: an observational study - Mikael Anne Greenwood-Hickman; Rod L. Walker; Abisola E. Idu; John Bellettiere; David Wing; Susan M. McCurry; Paul K. Crane; Eric B. Larson; Dori E. Rosenberg; Andrea Z. LaCroix (BMC Public Health)
Abstract Background Cross-sectional studies suggest that chronic disease burden in older adults is associated with lower activity. However, preceding life-course patterns of morbidity accumulation may also influence current activity and have not been well characterized. Using a well-described sample of older adults, we estimated associations between current chronic disease burden and accelerometer-measured moderate-to-vigorous intensity movement measures, light-intensity movement measures, and sedentary behavior measures. Additionally, we examined historic morbidity patterns among those with current multimorbidity to provide additional understanding of these later life associations between current multimorbidity and activity. Methods Analyses included N = 886 older adult study participants who wore activPAL and Actigraph accelerometers. We calculated Charlson Comorbidity Index (CCI; range 0–29) scores for participants at the time of device wear and estimated the association between current chronic disease burden (CCIcurrent) and each accelerometer-based activity metric using linear regression. Additionally, for participants categorized as having multimorbidity at time of device wear (CCIcurrent = 2+), we calculated CCI scores from age 55 through age at device wear. We plotted these to illustrate historic patterns of morbidity accumulation, and we compared activity metrics between participants with observed distal vs. recent onset of multimorbidity. Results A unit increment in CCIcurrent was associated with higher mean sitting bout duration (0.5 min, CI: [0.0,1.0], p = 0.039) and with both lower average daily step counts (-319 steps, CI: [-431,-208], p < 0.001) and lower average daily minutes of moderate-to-vigorous physical activity (MVPA; -3.8 min, CI: [-5.2,-2.4], p < 0.001). No associations were seen with standing, light-intensity physical activity, or other sitting measures. Among older adults with multimorbidity at time of device-wear, results suggested some evidence that participants whose apparent onset was more distal engaged in less MVPA (-12.1, CI: [-21.0, -3.2], p = 0.008) and had fewer daily steps (-1000, CI: [-1745, -254], p = 0.009) than participants whose apparent onset was more recent. Conclusions Current chronic disease burden was associated with moderate-to-vigorous intensity movement measures and some patterns of prolonged sitting. Current multimorbidity is characterized by a preceding pattern of accumulation over the life-course. Attention to both current and historic trajectory of multimorbidity is important in investigations of MVPA and health.